Mitochondrial Syndromes with Leukoencephalopathies - Wong, Lee-Jun C. (Seminars in Neurology, 2012)
White matter involvement has recently been recognized as a common feature in patients with multisystem mitochondrial disorders that may be caused by molecular defects in either the mitochondrial genome or the nuclear genes. It was first realized in classical mitochondrial syndromes associated with mitochondrial DNA (mtDNA) mutations, such as mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes (MELAS), Leigh's disease, and Kearns-Sayre's syndrome. Deficiencies in respiratory chain complexes I, II, IV, and V often cause Leigh's disease; most of them are due to nuclear defects that may lead to severe early-onset leukoencephalopathies. Defects in a group of nuclear genes involved in the maintenance of mtDNA integrity may also affect the white matter; for example, mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) caused by thymidine phosphorylase deficiency, Navajo neurohepatopathy (NNH) due to MPV17 mutations, and Alpers syndrome due to defects in DNA polymerase gamma (POLG). More recently, leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation (LBSL) has been reported to be caused by autosomal recessive mutations in a mitochondrial aspartyl-tRNA synthetase, DARS2 gene. A patient with leukoencephalopathy and neurologic complications in addition to a multisystem involvement warrants a complete evaluation for mitochondrial disorders. A definite diagnosis may be achieved by molecular analysis of candidate genes based on the biochemical, clinical, and imaging results.
Keywords: mitochondrial leukoencephalopathy; mitochondrial disorders; Leigh's disease; POLG; MNGIE; MPV17; DARS2